Nonlinear fracture assessment and nanomechanical deformation of elastomeric composites: Development of finite element model and experimental validation. Issue 7 (25th April 2021) - Goswami, Mohit; Ghorai, Sanjoy Kumar; Sharma, Sujit; Chakraborty, Goutam; Chattopadhyay, Santanu
Abstract: In this article, Mode‐I fracture and nanomechanical deformation of elastomeric composites are studied using nonlinear fracture mechanics implicating computer modeling techniques like finite element analysis, and the models developed are verified experimentally. The effect of low notch‐to‐width ratios (NWR) on failure properties like J‐integral, geometry factor, crack tip opening displacement (CTOD), crack advancement, and R‐curves is investigated. The geometry factor is found to be decreasing by 96% when NWR is increased from 0.06 to 0.34. An empirical relationship between CTOD and crack advancement for hybrid elastomeric composites depending on NWR is developed and has been verified analytically. Optimization of silica in 10 phr carbon black filled styrene butadiene rubber is performed, and several characterization techniques are used to justify the outcome. The applicability of mechanical properties like stress contours and factor of safety in fracture characterization of composites is explained briefly. A mesh sensitivity based finite element model has been developed for calibrating the nanoindentation test of elastomeric composites and verified experimentally. Abstract :